Bidhan Supreme and Bidhan Super: New brinjal varieties - Chattopadhyay, Arup; Dutta, Subrata; Mandal, Asit Kumar; Maurya, Praveen Kumar; Banerjee, Swadesh; Bhattacharjee, Tridip; Hazra, Pranab (Indian Horticulture, 2020)
Bidhan Supreme and Bidhan Super have been developed through selection from indigenous collections obtained from Dhenkanal district of Odisha and Murshidabad district of West Bengal, respectively, by Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal. These two varieties have been released by the State Variety Release Committee, West Bengal and notified by the Central Variety Release Committee for State release during 2019. Varieties are early maturing, soft textured, less seeded, spineless, and high yielding. These can be fitted well in multiple cropping system. These two varieties performed well in eastern parts of India apart from West Bengal.